2007
DOI: 10.1097/01.ta.0000240449.23201.57
|View full text |Cite
|
Sign up to set email alerts
|

Helicopter Emergency Medical Services (HEMS): Impact on On-Scene Times

Abstract: Combined EMS/HEMS assistance at an injury scene is associated with longer OST. When corrected for severity of injury and patient characteristics, no influence of longer OST on mortality could be demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
73
4
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 19 publications
4
73
4
1
Order By: Relevance
“…This paper was submitted without consulting the two trauma centers with an HEMS which prehospitally treated the patients involved in this study. Furthermore, previous papers [2,3,4] from other trauma centers showed conclusions that are very different to this study. Since this article is based on research on the effectiveness of the HEMS in the Netherlands, and the research was performed neither with involvement, nor information of one of the four HEMS stations, we like to make some remarks on this article from the perspective of the four HEMS stations.…”
contrasting
confidence: 53%
See 1 more Smart Citation
“…This paper was submitted without consulting the two trauma centers with an HEMS which prehospitally treated the patients involved in this study. Furthermore, previous papers [2,3,4] from other trauma centers showed conclusions that are very different to this study. Since this article is based on research on the effectiveness of the HEMS in the Netherlands, and the research was performed neither with involvement, nor information of one of the four HEMS stations, we like to make some remarks on this article from the perspective of the four HEMS stations.…”
contrasting
confidence: 53%
“…Table 1 showed us the dispatch criteria for HEMS, but the reality in the Netherlands is that only a few of the accidents present on the list result in an activation of the HEMS, as Ringburg etal. [3] showed earlier that only in 14% of the indications a HEMS has been activated. Lemson etal.…”
Section: Recently We Received the Following Publication In This Journmentioning
confidence: 99%
“…[2] When comparing the mean on-scene times of both the Netcare 911 HEMS operations with other similarly staffed operations, the mean on-scene times for the Netcare operations were often shorter. [7,20,21] An interesting finding was the similarity between the interfacility transfer and primary transfer on-scene times. The transfer times from scene to hospital for both the Netcare 911 HEMS operations were similar to another SA study.…”
Section: Discussionmentioning
confidence: 99%
“…However, many studies have described that doctor‐staffed helicopter use is beneficial for patients with cardiac arrest,5 trauma,1, 2, 3, 4, 6, 7, 8, 9 stroke,10, 11 and acute coronary syndrome 12. This research has reported a decrease in mortality rates and a reduction in the time to tertiary treatment for critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…According to our survey, 68% of patients with these four diseases were treated by a doctor‐staffed ambulance, although various criteria were used. However, a few studies have denied any benefits for trauma patients13 and have cautioned regarding longer on‐scene times 9…”
Section: Discussionmentioning
confidence: 99%